The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acschemneuro.6b00399
|View full text |Cite
|
Sign up to set email alerts
|

A Direct in Vivo Comparison of the Melanocortin Monovalent Agonist Ac-His-DPhe-Arg-Trp-NH2 versus the Bivalent Agonist Ac-His-DPhe-Arg-Trp-PEDG20-His-DPhe-Arg-Trp-NH2: A Bivalent Advantage

Abstract: Bivalent ligands targeting putative melanocortin receptor dimers have been developed and characterized in vitro, however studies of their functional in vivo effects have been limited. The current report compares the effects of homobivalent ligand CJL-1-87, Ac-His-DPhe-Arg-Trp-PEDG20-His-DPhe-Arg-Trp-NH2, to monovalent ligand CJL-1-14, Ac-His-DPhe-Arg-Trp-NH2 on energy homeostasis in mice after central intracerebroventricular (ICV) administration into the lateral ventricle of the brain. Bivalent ligand CJL-1-87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(73 citation statements)
references
References 122 publications
5
68
0
Order By: Relevance
“…Synthetic cyclic MSH derivatives [ 22 , 176 ], such as setmelanotide [ 53 , 54 , 55 , 56 ] or bremelanotide (also termed PT-141, Vyleesi, Rekynda; a cyclic heptapeptide derivative of MSH [ 29 ] that has been approved for the treatment of female hypoactive sexual desire disorder [ 29 , 177 , 178 , 179 ]), and multivalent [ 59 , 60 ] as well as non-peptidic MC4R ligands [ 63 , 180 ], were developed for pharmacological treatment options using the MC4R as a target. Notably, different MC4R ligands may be associated with differentially initiated signaling pathways, as already shown for setmelanotide, which varies from α-MSH in its signaling profile [ 39 ].…”
Section: Specific Features In the Mc4r Sequence And Structure Linkmentioning
confidence: 99%
“…Synthetic cyclic MSH derivatives [ 22 , 176 ], such as setmelanotide [ 53 , 54 , 55 , 56 ] or bremelanotide (also termed PT-141, Vyleesi, Rekynda; a cyclic heptapeptide derivative of MSH [ 29 ] that has been approved for the treatment of female hypoactive sexual desire disorder [ 29 , 177 , 178 , 179 ]), and multivalent [ 59 , 60 ] as well as non-peptidic MC4R ligands [ 63 , 180 ], were developed for pharmacological treatment options using the MC4R as a target. Notably, different MC4R ligands may be associated with differentially initiated signaling pathways, as already shown for setmelanotide, which varies from α-MSH in its signaling profile [ 39 ].…”
Section: Specific Features In the Mc4r Sequence And Structure Linkmentioning
confidence: 99%
“…These probes may take advantage of the aggregation or “clumping” of multiple receptors together on the cell membrane (Figure 5 D-E). Recent studies have suggested the presence of melanocortin receptors dimers (or higher-order oligomers) for every known melanocortin subtype [207-214]. Furthermore, radiolabeled ligand binding studies suggest that there are two tandem binding sites with different binding properties on cells expressing melanocortin receptors, indicating targetable dimers [215, 216].…”
Section: Bivalent and Multivalent Melanocortin Ligandsmentioning
confidence: 99%
“…Administration of CJL-1-87 icv resulted in dose-dependent decreased food intake [134]. Comparison to the monovalent ligand Ac-His-DPhe-Arg-Trp-NH 2 suggested little improvement in a nocturnal feeding paradigm [108, 134, 214]. However, a direct comparison study utilizing a fast-refeeding paradigm showed significant differences between CJL-1-87 and Ac-His-DPhe-Arg-Trp-NH 2 after ICV administration [214].…”
Section: Bivalent and Multivalent Melanocortin Ligandsmentioning
confidence: 99%
See 2 more Smart Citations